PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF MATA PELAJARAN IPAS PADA KURIKULUM MERDEKA DI KELAS IV SDN 09 SITIUNG - Anggrayni, M.; Putri, Suci Rahma; Fitriani, Fitriani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to develop interactive learning videos using powerpoint applications in science learning in the Merdeka Curriculum class IV SDN 09 Sitiung. Because the results of observations and interviews with the homeroom teacher of class IV showed that the learning was low, learning videos really helped increase students' interest in learning with a total of 8 students. Research and Development (R&D) method in the ADDIE model which has important steps contained in it, namely: 1. The stage of needs analysis, student characteristics, and curriculum (Analyze) 2. learning design stage ( Design), 3. development stage is developing video products by testing validity in the form of questionnaires (language, content/construct, and graphics), by obtaining the percentage score from the three validators on average 85% in the